Sustained Effectiveness of Cilostazol After Endovascular Treatment of Femoropopliteal Lesions: Midterm Follow-up From the Sufficient Treatment of Peripheral Intervention by Cilostazol (STOP-IC) Study. (June 2018) - Soga, Yoshimitsu; Hamasaki, Toshimitsu; Edahiro, Ryuya; Iida, Osamu; Inoue, Naoto; Suzuki, Kenji; Yokoi, Yoshiaki; Kawasaki, Daizo; Zen, Kan; Urasawa, Kazushi; Aodo, Kenji
Purpose: To investigate the midterm safety and effectiveness of cilostazol treatment in claudicant patients undergoing endovascular therapy.Methods: The Sufficient Treatment of Peripheral Intervention by Cilostazol (STOP-IC) study ( ClinicalTrials.gov identifier NCT00912756; University Hospital Medical Information Network identifier UMIN000002091) enrolled 200 patients (mean age 73 years; 131 men) treated for femoropopliteal disease from March 2009 to April 2011 at 13 cardiovascular centers in Japan. The participants were randomized 1:1 to receive oral aspirin with or without cilostazol. Of the 100 patients assigned to the 2 treatment groups, 7 patients in the cilostazol group and 2 patients in the no-cilostazol group were withdrawn from the study without undergoing endovascular treatment, leaving 93 patients in the cilostazol group and 98 patients in the no-cilostazol group for follow-up analysis. The primary outcome measure was primary patency; secondary outcome measures were freedom from clinically-driven target lesion revascularization (CD-TLR) and overall survival. Outcomes were analyzed on an intention-to-treat basis using the Kaplan-Meier method; estimates were compared with the log-rank test.Results: The median follow-up was 38.1 months (interquartile range 25.1, 47.7). Among the 93 subjects in the cilostazol group, 7 died and 26 withdrew from administration 1 year after the endovascular procedure. Discontinuation of cilostazol was not a significant factor for restenosis. Primary patency was significantly higher in the cilostazol group than in the no-cilostazol group (69% vs 54%, p=0.026) at 3 years. The cilostazol group also had better 3-year freedom from CD-TLR (78% vs 63%, p=0.014), although overall survival estimates did not differ significantly (p=0.95).Conclusion: These results suggest that the safety and effectiveness of cilostazol treatment were sustained in patients with femoropopliteal disease undergoing endovascular treatment.